THE EFFECT OF SEMENDO COFFEE ON THE NUMBER OF FIBROBLAST CELLS IN GINGIVA WOUND OF RATS - Sulistiawati Sulistiawati; Hema Awalia; Ulfa Yasmin; Rosada Sintya Dwi; Alya Namira (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Gingiva is a keratinized epithelium tissue that surrounds the tooth and protects the tissue beneath it, which is often wounded. Sumatran robusta coffee, semendo coffee, consists of active compounds such as polyphenol, alkaloid, and saponin that can increase fibroblast amount during the wound healing process. This study aims to determine the effect of semendo coffee (Coffea canephora) extract on fibroblast amount on gingiva wound of Rattus norvegicus. Methods: The true experimental study with a post-test-only control group design was confirmed in this study. This study used twenty-four rats (Rattus norvegicus) divided into 4 groups. The gingival injury was performed on mandible gingiva using a punch biopsy method with a 2mm diameter. The gel was given according to the treatment group 2 times a day for 7 days. Semendo coffee extract at 5%, 20%, and 40%, was applied to the wound treatment groups, while placebo gel was applied to the control group. Euthanasia was delivered on the 8th day, then histological preparation was made. The amount of fibroblast was analyzed by Olympus software. Result: The results showed that the Semendo coffee extract could significantly improve the number of fibroblast cells compared to the control groups. The highest fibroblast amount was found in the group with Semendo coffee extract at a concentration of 40%. Conclusion: Semendo coffee extract at 5%, 20%, and 40% increased the amount of fibroblast on the gingival wound in Rattus norvegicus.